EKSISTENSI DAN PROSES PERADILAN HAM DI INDONESIA - I Wayan Santoso (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2022)
The development of the influence of human rights in its journey has affected various countries, including Indonesia. The end of the New Order government, which was very repressive after 32 years in power, has raised awareness of the importance of respecting human rights. Demands for justice against past human rights violators are increasing, while human rights violations continue to take place in various forms, patterns and different actors. Human rights issues are often used by a group of people for their political and economic interests, while officials are reluctant to act for fear of being accused of violating human rights. The understanding of human rights in Indonesia as values, concepts and norms that live and develop in society can be traced through a study of years, and before the human rights court was formed, cases of gross human rights violations were tried by an authorized general court. The establishment of legal regulations regarding gross human rights violations and the establishment of a human rights court is necessary because the applicable legal regulations, most of which are rules from the Dutch colonial era, such as the Criminal Code, do not regulate gross human rights violations as extraordinary crimes. but only regulates conventional crimes, such as murder as regulated in Article 338 of the Criminal Code, persecution as regulated in Article 351 of the Criminal Code. Kidnapping as regulated in Article 333 of the Criminal Code, rape as regulated in Article 285 of the Criminal Code, etc. So in this case, of course, there is a difference between the prosecution process in criminal law and the prosecution process in cases of gross human rights violations. In order to provide protection, certainty, justice and a feeling of security to individuals or the community, it is necessary to establish a Human Rights Court and the rule of law. In Indonesia, the existence of Law Number 39 of 1999 concerning Human Rights (UU HAM) and Law Number 26 of 2000 concerning the Human Rights Court (Law on the Human Rights Court) is expected to protect human rights, both individuals and communities and become the basis for enforcing , legal certainty, justice and a feeling of security for individuals and the community against serious human rights violations